Daily medication routine of adolescents with HIV/AIDS - Cristiane Cardoso de Paula; Stela Maris de Mello Padoin; Crhis Netto de Brum; Clarissa Bohrer da Silva; Paulo Victor Cesar de Albuquerque; Renata de Moura Bubadué (Universidade Federal de Goias, 2013)
The objective of this study was to describe the sociodemographic, clinical, and behavioral characteristics of the daily medication routine of adolescents with HIV/AIDS of ages 13 to 19 years, followed at a reference service. This descriptive cross-sectional study was performed with 23 adolescents, using a quantitative approach. Data were collected using a form during appointments at the outpatient clinic. Univariate analysis revealed: females, in the initial phase of adolescence, and vertical transmission. The highlights were: lack of assiduity to appointments; unprotected sex; and consumption of alcohol. Regarding the daily medication routine, subjects depend on their parents or guardians, use strategies to remember to take the medications, and are unaware about the laboratory test for disease management and treatment. There is a need for educative intervention using information and communication technology, such as the Internet, to promote health and autonomy among adolescents. Descriptors: Acquired Immunodeficiency Syndrome; Adolescent Health; Antiretroviral Therapy, Highly Active; Nursing.